"Fundamental British Values": What's Fundamental? What's Value? and What's (Now) British?. Issue 1 (May 2020) - Stronach, Ian; Frankham, Jo
Here we give shallow answers to the 'deep' questions raised in the title of this piece. We slight the question of 'value' as mainly 'interested commodities' and throw darkness rather than light on the now increasingly troubled question of 'British' identity. Our approach is not to define "Fundamental British Values" (FBV) (as we will show, that proved impossible) but to represent the multiplicity of contradictory contents that invest its form. In such a "performative agonistics", we anticipate a dissemination rather than an insemination of meaning in contrast with the ongoing neoliberal "rage for certainty". "Fundamental British Values, " in Badiou's terms, is a polysemous "event, " whose performances and contexts should be regarded within a series of theatrical metaphors—an "amphitheatre" of meanings, perhaps, in a "post-truth" world. Thus, these deconstructions should be seen as part of a more generic critique of neoliberal enclosures that seek for definitions, essences, identities, and quantifications.